Cetaceans in the Southern California Bight : behavioral, acoustical and spatio-temporal modeling - Henderson, E. Elizabeth (eScholarship, University of California, 2010)
This dissertation examines the behavior, occurrence patterns, and distribution of small cetaceans in the Southern California Bight (SCB) across a variety of temporal and spatial scales in order to elucidate how they interact with their environment. I begin by correlating the surface behavior and vocalizations of two exemplar species, the common dolphin (Delphinus sp.) and the Pacific white-sided dolphin (Lagenorhynchus obliquidens). Surface behaviors of both species were classified based on their rates and types of vocalizations using random forest decision trees. Common dolphins were shown to travel predominantly throughout the day, with an off-shore movement at night and in-shore movement in the morning, and are likely feeding at night on the scattering layer. Vocalizations were most abundant and complex in fast traveling, spread-out groups, and were lowest during foraging. The two Pacific white-sided dolphin "click type" groups demonstrated distinctly different behavioral patterns and vocalizations, with one foraging during the day and the other likely foraging at night. I go on to examine the occurrence patterns of all marine mammals encountered in the SCB in 2006, 2007 and 2008 from the R/P FLIP in relation to the local oceanography and biology. 2006 had warm ocean temperatures and the most encounters of all marine mammal species, while 2007 was the coolest, most stratified year with the highest chlorophyll levels, and had high baleen whale encounter rates but low delphinid encounter rates. 2008 was the warmest year with a deep mixed layer and deep chlorophyll maximum, with a moderate level of observations of common dolphins, Pacific white-sided dolphins, and some baleen whales, but high numbers of California sea lions (Zalophus californicus). Also in 2008, net tows and sonar scans were added to examine the zooplankton and fish biomass around FLIP. Non- eucalanid copepods and siphonophores dominated the zooplankton biomass, while anchovy (Engraulis mordax) and jack mackerel (Trachurus symetricus) were presumed to dominate the fish biomass. Finally, I explore the distributions of eight species of small cetaceans throughout the SCB using a combined 30-year dataset from CalCOFI and SWFSC cruises. I model the distribution of each species against PDO, ENSO, and seasonal sea-surface temperature indices as well as depth metrics. All eight species demonstrated changes in their distributions relative to the three temperature shifts, offering insight into possible responses to future climate change shifts and ocean warming